How Urban Communities Debate Waste: Learning from the CSR Agroeduwisata Jayakarta Program - Wina, Ni Made Ayu; Yuliani; Yahya, Fahruri; Ananda, Fatika Hastigerina; Ekarini, Farina (Global Writing Academica Researching and Publishing, 2024)
Several studies on waste issues in the Global South still echo a pessimistic voice about waste management. Few citizens of the Global South view waste not merely as dirty objects but as valuable residual resources. This single case study reveals something different. The waste management practices carried out by two urban community groups in East Jakarta, Indonesia, namely Kelompok Tani Hutan (KTH) of Rumah Kaum Jayakarta and Bank Sampah Pintar (BSP) of Pok Lisa in the Agroeduwisata Jayakarta Program, show that these groups have views and practices of waste management that are not only environmentally beneficial but also economically and culturally advantageous. This program was implemented and developed in collaboration with CSR PT ANTAM Tbk UBPP Logam Mulia. The findings of this study show that waste is treated not as dirty and damaged material but can instead be converted into gold. The practices carried out by the groups in this program align with the concept of sustainable city development.